2021
DOI: 10.3389/fcell.2021.650819
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of ATM-Mediated Autophagy in the Transition From Hyper-Radiosensitivity to Induced Radioresistance in Lung Cancer Under Low-Dose Radiation

Abstract: Objective: This study aimed to investigate the effect of ataxia telangiectasia mutated (ATM)–mediated autophagy on the radiosensitivity of lung cancer cells under low-dose radiation and to further investigate the role of ATM and its specific mechanism in the transition from hyper-radiosensitivity (HRS) to induced radioresistance (IRR).Methods: The changes in the HRS/IRR phenomenon in A549 and H460 cells were verified by colony formation assay. Changes to ATM phosphorylation and cell autophagy in A549 and H460 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A similar conclusion can be reached with the cell cycle since all the cell lines have been irradiated in similar distributions of cell cycle phases. Our results were found to be in agreement with literature data [28][29][30] (Figure 2). 2 were fitted to S(D) = exp(−αres (1 + g exp(−D/Dc))D−βD 2 ) (Formula (2)).…”
Section: Hrs Status Of the 6 Tumor Cell Lines Used In This Studysupporting
confidence: 93%
“…A similar conclusion can be reached with the cell cycle since all the cell lines have been irradiated in similar distributions of cell cycle phases. Our results were found to be in agreement with literature data [28][29][30] (Figure 2). 2 were fitted to S(D) = exp(−αres (1 + g exp(−D/Dc))D−βD 2 ) (Formula (2)).…”
Section: Hrs Status Of the 6 Tumor Cell Lines Used In This Studysupporting
confidence: 93%
“…AMBRA1 as an emerging haploinsufficient tumor suppressor plays a pivotal role in tumorigenesis and progression ( 26 , 45 ). Furthermore, AMBRA1-mediated autophagy plays controversial roles in chemoradiotherapy ( 78 , 79 , 81 84 ), and the different roles of AMBRA1-associated autophagy in cancer treatment seem to depend on tumor type, stage, and genetic context ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is another classical cancer treatment scheme, and AMBRA1 also regulates tumor sensitivity to radiotherapy. AMBRA1-associated autophagy promotes the transition from hyper-radiosensitivity to induced radio-resistance in A549 and H460 human lung adenocarcinoma cell lines ( 84 ). Calcitriol, an active metabolite of vitamin D, enhances the sensitivity to irradiation in SiHa and CaSki cervical cancer cells by promoting AMBRA1 degradation ( 85 ).…”
Section: Ambra1—a Potential Target For Anticancer Therapymentioning
confidence: 99%
“…However, recent evidence has strongly linked ATM to the induction and function of autophagy in response to genotoxic stress (reviewed in depth in [ 62 , 63 ]). For example, ATM regulates radiation-induced autophagy through the mTOR pathway [ 64 , 65 ], MAPK14 pathway [ 66 ], JNK pathway [ 67 ], and PI3KIII pathway [ 68 ], and complete lack of ATM function results in the failure of autophagy induction in tumor cells [ 68 , 69 , 70 ] or switches the cell stress response to senescence [ 71 ]. Conversely, Goehe et al showed that ATM knockdown attenuates both autophagy and senescence in response to chemotherapy [ 69 ], suggesting a more complicated role of ATM in regulating autophagy.…”
Section: Discussionmentioning
confidence: 99%